Dimensions of Resilience in Developing Countries Informality, Solidarities and Carework - Charmes, Jacques; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides the latest empirical data on the three forms of resilience: informality, solidarities and unpaid care-work. It uncovers and quantifies these three forms of resilience that are generally invisible or ill recognised, whereas these play a major role in the livelihoods of poor and vulnerable populations. The book shows how the slow but constant unveiling of these forms over the past four decades has gradually changed our vision of progress and development and is impacting the norms and concepts that shape our vision of the economy and society. The book also emphasizes the role of informal economy through explaining the origins of the concept, its definitions and the methods of data collection and measurement. As such the book will be of interest to students, researchers and policy makers in population studies, economics, and international development.
Introduction -- Part 1: Informality -- Chapter 1: History of a Concept -- Chapter 2: Concepts, Methodologies, Sources of Data -- Chapter 3: Trends and Characteristics of Informal Employment and its Components -- Chapter 4: Role of Informal Employment in Economic Development and Development Policies -- Part 2: Solidarities -- Chapter 5 -- Community, Individualism and Social Capital -- Chapter 6: Concepts, Methodologies and Sources of Data -- Chapter 7: Transfers, Remittances and Care -- Chapter 8: Towards a Social Protection Floor for All -- Part 3: Women's Activities and Unpaid Work -- Chapter 9: Female Participation Rates to the Labour Force and to Informal Employment: Reasons for their Underestimation -- Chapter 10: The Extended Notion of Work and The Time-Use Surveys -- Chapter 11: Feminisation of Poverty, Time Poverty and Potential For Development -- Chapter 12: Towards Recognition of Women's Work and Women's Empowerment -- Conclusion -- Bibliography -- General Index.
Keywords: Demography; Population; Population -- Economic aspects; Population and Demography; Population Economics